Land, stories, and resorces : discourse and entification in Onabasulu modernity. - Ernst, Thomas M. (American Antropological Association, 1999)
Resource development may involve codifications of social organization that alter preexisting arrangements. This is the case in Onabasulu society today, impacted by Chevron's petroleum extractions nearby and the codifications of collective life introduced by multinationals and the State of Papua New Guinea alike. Located on the Great Papuan Plateau of Papua New Guinea, Onabasulu ÒclansÓ are largely an artifact of a certificate-based incorporation process and do not preexist the era of petroleum development. This ÒentificationÓ of clans is matched by an entification of ethnic groups, which previously enjoyed soft (or ÒthickÓ) rather than hard (or sharp) edges and boundaries. Various discoursesÑlineage histories, myths, other storiesÑare best viewed as instruments that political actorsÑthe Onabasulu as a people, various clans, various individualsÑuse to embrace, contest, or manipulate the new codifications as these actors strive to position themselves competitively in relation to resources in an era of nationalist and capitalist penetration. ÒLand, Stories, and ResourcesÓ argues for a discourse-centered political ecology of Onabasulu modernity, one that recognizes the political and discursive roots of human-land relations in an unfolding and open-ended history predicated on an emerging politics of difference within a globalizing context,